Open Educational Resources as a Global Solution for Wider Class Courses - Ouahib, Sara; EL Kharki, Khadija; Bendaoud, Rachid; Burgos, Daniel; Berrada, Khalid (Lecture Notes in Educational Technology, 2023)
Since their appearance about two decades ago, open educational resources (OER) have become a part of a rapidly growing movement as more nations and institutions adopt the view that educational research and content belong to all people, regardless of their location or financial situation, and that content should be open and accessible to all. This movement can profoundly impact educational practices and practitioners, not only by making educational resources available and accessible but also by ensuring continuous improvement of the quality of these resources by providing a legal framework for preserving users’ rights, thus enabling users to become creators, rather than mere consumers of content. To reach this goal, it is necessary to establish creative and innovative pedagogical thinking and practices. Although OER are not a panacea for all educational problems, they can play an important, even essential role, in improving access and quality in higher education. Since 2016, the Cadi Ayyad University (UCA), Morocco, has been utilizing OER and adopting open educational practices (OEP) in the educational system. In this chapter, we discuss the concept of OER as a comprehensive solution to widening access to education and use of OER to overcome problems of massification within UCA. Then, we present OER-based initiatives launched and developed by UCA in this context.
Keywords: Cadi Ayyad University; higher education; open education; open educational resources; open educational resources adoption; pedagogical innovation; Scopus(2)